2019
DOI: 10.1039/c9ob00647h
|View full text |Cite
|
Sign up to set email alerts
|

Covalently linked meso-tetraaryl triphyrin(2.1.1)-ferrocene(s) conjugates: synthesis and properties

Abstract: Functionalized meso-tetraaryl triphyrins(2.1.1) containing two meso-iodophenyl groups or a bromo group at the β-pyrrole carbon were synthesized over a sequence of steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…Compounds 2–7 were further characterized by 1 H, 13 C, and 1 H– 1 H COSY NMR (Figures S1–S22), and the 1 H NMR spectra of compounds 2–7 along with triphyrin(2.1.1) 1 in the selected region are presented in Figure . In the 1 H NMR spectrum, the six β-pyrrole protons of triphyrin(2.1.1) 1 showed three sets of resonances at 7.52 ppm (types d and e), 7.63 ppm (types a and b), and 8.20 ppm (types c and f) . Monobrominated triphyrin(2.1.1) 2 showed one singlet at 7.51 ppm (type b) and four doublets at 7.42 ppm (type e), 7.46 ppm (type d), 8.02 ppm (type f), and 8.14 ppm (type c) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compounds 2–7 were further characterized by 1 H, 13 C, and 1 H– 1 H COSY NMR (Figures S1–S22), and the 1 H NMR spectra of compounds 2–7 along with triphyrin(2.1.1) 1 in the selected region are presented in Figure . In the 1 H NMR spectrum, the six β-pyrrole protons of triphyrin(2.1.1) 1 showed three sets of resonances at 7.52 ppm (types d and e), 7.63 ppm (types a and b), and 8.20 ppm (types c and f) . Monobrominated triphyrin(2.1.1) 2 showed one singlet at 7.51 ppm (type b) and four doublets at 7.42 ppm (type e), 7.46 ppm (type d), 8.02 ppm (type f), and 8.14 ppm (type c) .…”
Section: Resultsmentioning
confidence: 99%
“…Triphyrin­(2.1.1) 1 is the lower member of the porphyrinoid family containing three pyrrole rings connected via four meso carbons. Triphyrin(2.1.1) 1 is a 14π-electron aromatic macrocycle , and exhibits physicochemical properties similar to those of porphyrins. The triphyrins(2.1.1) are monoanionic tridentate ligands with a cavity size smaller than that of 18π-tetrapyrrolic porphyrins(1.1.1.1) but have the ability to form coordination complexes like porphyrins. ,,− The recently developed (2+1) synthetic strategy reported by our group is very useful for preparing any desired meso -tetraaryl triphyrins(2.1.1) readily, and the chemistry of triphyrins(2.1.1) can now easily be exploited. The electronic properties of triphyrins(2.1.1) can be altered further upon introduction of a specific substituent(s) at the β-pyrrole carbons . One approach to the synthesis of pyrrole-substituted triphyrins(2.1.1) is by using substituted pyrroles as key precursors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the triphyrin(2.1.1)­s such as meso -tetraaryl bicyclo[2.2.2]­octadiene­(BCOD)-fused-triphyrin(2.1.1)­s and meso -tetraaryl triphyrin(2.1.1)­s were initially formed serendipitously, researchers have optimized the conditions to obtain triphyrin(2.1.1)­s in good yields and demonstrated that the triphyrin(2.1.1)­s are indeed good coordinating ligands by synthesizing Ru­(II), Re­(I), Mn­(I), Fe­(II), Pd­(II), Pt­(II), Pt­(IV), Ir­(III), and B­(III) triphyrin(2.1.1) complexes (Chart ). Recently, we established a simple and straightforward [2 + 1] condensation method for the synthesis of β-free meso -tetraaryl [14]­triphyrin(2.1.1)­s 1–3 in good yields using readily available precursors as shown in Scheme . Our approach now would allow to synthesize any desired meso -tetraaryl triphyrin­(2.1.1)­s in reasonable yields.…”
Section: Introductionmentioning
confidence: 99%